2016
DOI: 10.5901/mjss.2016.v7n1s1p406
|View full text |Cite
|
Sign up to set email alerts
|

Prospects for Increasing Commercial Mushroom Production in Malaysia: Challenges and Opportunities

Abstract: One of the benefits of mushroom cultivation is their potential contribution to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
1
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 11 publications
(28 reference statements)
0
41
1
9
Order By: Relevance
“…A number of these species have appeared as mushrooms products on the shelves in supermarkets (S1 Fig) and been cooked in the daily life (S2 Fig). In recent years, artificial cultivation of edible mushrooms with the benefits of short growing times, very low inputs requirements for production, prevailing external climatic and easy production technologies has become more and more popular in many regions due to an increasing awareness on the usage of them [46]. The quality of cultivated edible mushrooms is becoming an object of public concern.…”
Section: Introductionmentioning
confidence: 99%
“…A number of these species have appeared as mushrooms products on the shelves in supermarkets (S1 Fig) and been cooked in the daily life (S2 Fig). In recent years, artificial cultivation of edible mushrooms with the benefits of short growing times, very low inputs requirements for production, prevailing external climatic and easy production technologies has become more and more popular in many regions due to an increasing awareness on the usage of them [46]. The quality of cultivated edible mushrooms is becoming an object of public concern.…”
Section: Introductionmentioning
confidence: 99%
“…Di Malaysia, terdapat ramai usahawan menceburi perusahaan cendawan atas dasar minat yang begitu mendalam dan untuk menjana sumber pendapatan namun tahap kejayaan kebanyakan daripada mereka adalah kurang menyerlah. Ini disebabkan oleh kekurangan ilmu pengetahuan berkaitan pengurusan tanaman dan pengurusan lepas tuai; kurang inovasi; tidak bersifat kreatif; dan skop industri yang tidak bersifat komersil (Rosmiza et al, 2016). Justeru, kepentingan penyertaan institusi kerajaan mahupun swasta dilihat sangat relevan memandangkan kebanyakan usahawan kekurangan modal dan kemahiran untuk menguasai pasaran (Rosmiza et al, 2015).…”
Section: Kecenderungan Penglibatan Usahawan Dalam Industriunclassified
“…The second is that inadequacy of technological performance influencing yield productivity (Nugroho, 2013 ;Arminsyurita, 2014 ;Iriantinah, 2014). By using the same tool of analysis, outside Indonesia, other authors also stated that mushroom industry such as in Malaysia and Turkey experience similar weakness (Celik & Peker, 2009 ;Rozmiza et al, 2016). Eventually these previous studies suggested to expand the scale and also to enhance technological aspect for gaining quality and quantity of production.…”
Section: Introductionmentioning
confidence: 99%